Self-identified gadolinium toxicity: comparison of gadolinium in bone and urine to healthy gadolinium-based contrast agent exposed volunteers. (27th November 2018) - Lord, Michelle L; McNeill, Fiona E; Gräfe, James L; Noseworthy, Michael D; Chettle, David R
Abstract: Objective : To report additional gadolinium bone and urine data that can contribute to gaps in knowledge with respect to gadolinium uptake and retention in the body. Approach : In vivo measurements of gadolinium retention in the tibia bone were performed on individuals self-identified as exhibiting symptoms of gadolinium toxicity as a result of receiving GBCA, as well as on control individuals. Gadolinium urine measurements for controls, symptomatic exposed, and non-symptomatic exposed were conducted through Mayo Medical Laboratories. Main results : Gadolinium bone concentration in the exposed group is significantly higher than the control group ( p < 0.01), with a significant difference between symptomatic and non-symptomatic ( p < 0.01), using a one-tailed t test on variance-weighted means. Gadolinium urine levels in both control subjects and non-symptomatic exposed subjects are significantly lower than symptomatic exposed subjects ( p ≤ 0.05). A linear regression analysis for gadolinium urine levels and GBCA dose resulted in a positive linear relationship ( R 2 = 0.91, p < 0.01). Gadolinium levels in urine and gadolinium concentration in bone were found to have a non-significant relationship ( R 2 = 0.11, p = 0.3). Significance : Significant differences in gadolinium levels in bone and urine are observed between individuals experiencing symptoms of gadolinium toxicity and for those who are not exhibiting symptoms. No correlation was observed between gadolinium in bone and gadolinium excreted in urine, suggesting that the retention of gadolinium in the body is complicated, involving multiple long-term storage sites.